The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/cyto.a.24298
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio spillover compensation in mass cytometry data

Abstract: Signal intensity measured in a mass cytometry (CyTOF) channel can often be affected by the neighboring channels due to technological limitations. Such signal artifacts are known as spillover effects and can substantially limit the accuracy of cell population clustering. Current approaches reduce these effects by using additional beads for normalization purposes known as single-stained controls. While effective in compensating for spillover effects, incorporating single-stained controls can be costly and requir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…However, recent publications have reported that signal spillover due to issues such as metal oxidation, abundancy related spillover, and metal impurities can impact data quality and interpretation in MC [ 52 , 69 ]. Efforts have been employed using single metal bead based controls [ 52 ], unlabeled competitor antibody [ 69 ], or statistical approaches [ 70 ] for compensating crosstalk between channels to improve overall data quality.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…However, recent publications have reported that signal spillover due to issues such as metal oxidation, abundancy related spillover, and metal impurities can impact data quality and interpretation in MC [ 52 , 69 ]. Efforts have been employed using single metal bead based controls [ 52 ], unlabeled competitor antibody [ 69 ], or statistical approaches [ 70 ] for compensating crosstalk between channels to improve overall data quality.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Normalized mass cytometry data files were further processed in R using the CytoSpill package v.0.1.0 to correct for any signal overlap between markers 66 . Next, corrected FCS files were imported into Cytobank (Cytobank) for manual gating on CD45 + single-cell events and major cell populations (Supplementary Table 8 ).…”
Section: Methodsmentioning
confidence: 99%
“…As some spatial platforms gather information on a per spot basis, several denoising software tools such as content-aware image restoration (CARE) [72], residual channel attention networks (RCAN) [73], and Noise2Void [74] can be applied to raw images to improve the quality especially in fluorescence based platforms. For mass cytometry based spatial platforms, data quality can be improved by spillover correction software [75]. For example, if the ground truth of spillover is known or empirically adjusted from the data, Reinforcement Dynamic Spillover EliminAtion (REDSEA) [76] leverages the spatial proximity of cells with signal that comes from generally mutually exclusive markers.…”
Section: Available General-purpose Software and Pipelinesmentioning
confidence: 99%